UPAYA PEMERINTAH DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK - Amrina, Eka; Furqon, Imahda Khoiri (Universitas Pembangunan Panca Budi, 2023)
Tax is one of the sources of state revenue that is used for government spending. The government has been trying to increase tax revenue. Tax revenue can be increased if the taxpayer has compliance in fulfilling tax obligations. The purpose of this paper is to find out how the government's efforts to improve taxpayer compliance. This research is a qualitative research and uses descriptive analysis method, as well as a data collection system using library research. The results show that the government's efforts to improve taxpayer compliance include issuing and sending warning letters, filing appeals, submitting tax bills, stimulating tax awareness society, improving the quality of tax service offices, helping taxpayers to fulfill tax administration obligations, tax socialization so as to provide comprehensive understanding to taxpayers understanding of their rights and obligations, simplifying the existing tax system, and conducting audits to assess the tax payable.